2017
DOI: 10.1051/0004-6361/201629473
|View full text |Cite
|
Sign up to set email alerts
|

Exoplanetary atmospheric sodium revealed by orbital motion

Abstract: Context. During primary transits, the spectral signatures of exoplanet atmospheres can be measured using transmission spectroscopy. We can obtain information on the upper atmosphere of these planets by investigating the exoplanets' excess sodium absorption in the optical region. However, a number of factors can affect the observed sodium absorption signature. We present a detailed model correcting for systematic biases to yield an accurate depth for the sodium absorption in HD 189733b. Aims. The goal of this w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 60 publications
1
62
0
Order By: Relevance
“…This is important since a transiting planet with no atmosphere can produce a transmission signal, even if there are no active regions present on the stellar surface, due to the fact that the ratio of the line core to the continuum changes as a function of the transit (see Figures 1-5 of Czesla et al 2015). This effect was recently included in Na I transit modeling by Khalafinejad et al (2016).…”
Section: Contrast and Limb-darkening/brighteningmentioning
confidence: 99%
“…This is important since a transiting planet with no atmosphere can produce a transmission signal, even if there are no active regions present on the stellar surface, due to the fact that the ratio of the line core to the continuum changes as a function of the transit (see Figures 1-5 of Czesla et al 2015). This effect was recently included in Na I transit modeling by Khalafinejad et al (2016).…”
Section: Contrast and Limb-darkening/brighteningmentioning
confidence: 99%
“…Here, we present high-resolution transit observations of the ultra-hot Jupiter WASP-121b (Delrez et al 2015) with the UV-Visual Echelle Spectrograph (UVES) at the Very Large Telescope (VLT; Dekker et al 2000), which has been previously used for measuring exoplanet spectra (e.g. Snellen 2004;Czesla et al 2015;Khalafinejad et al 2017;Gibson et al 2019). WASP-121b orbits a bright, V∼10.5 F6V host with a period of only 1.27 days, giving it an equilibrium temperature of over 2400 K. Coupled with its inflated radius, it is an excellent target for transmission spectroscopy.…”
mentioning
confidence: 99%
“…Snellen et al 2008;Redfield et al 2008), and the technique is rapidly growing in popularity (e.g. Cauley et al 2016;Casasayas-Barris et al 2017;Wyttenbach et al 2017;Khalafinejad et al 2017;Yan & Henning 2018). While insensitive to continuum features in the planet, and necessarily sacrificing signal-to-noise to observe at high resolution, this technique is arguably less sensitive to instrumental systematics, making it well suited to confirming features discovered at low-resolution.…”
mentioning
confidence: 99%
“…Here, we present results of observations of the exoplanet WASP-31b at high-resolution, using the UV-Visual Echelle Spectrograph (UVES) at the Very Large Telescope (VLT) (Dekker et al 2000), which has been previously shown to be sensitive to signatures of exoplanet atmospheres (e.g. Snellen 2004;Czesla et al 2015;Khalafinejad et al 2017). WASP-31b is an inflated hot-Jupiter discovered by Anderson et al (2011), with a mass and radius of ≈ 0.48 M J and 1.55 R J , respectively.…”
mentioning
confidence: 99%